Airborne and landing phases of a simplified back somersault movement. (July 2016) - Hemami, Hooshang; Khosravi-Sichani, Bahman; Barin, Kamran
Abstract: The issues of coordination, timing and control are addressed for a back somersault sagittal movement. The three-dimensional physical model is comprised of three segments for feet, torso, and hands. In the airborne phase, it is assumed that the head and the torso are held as one rigid body such that the angular velocities and accelerations, measured and estimated for the head, are the same as those of the torso. These physical states provide acceleration feedback to reduce rotational velocities before the landing phase. Successful stable airborne and landing phases are shown in a computer simulation.